P PENGARUH PEMBERIAN JUS BUAH BIT (BETA VULGARIS) TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA REMAJA PUTRI KELAS X IPS DI MAN 2 MODEL MEDAN TAHUN 2022 - Elvida Sulistiana; Husna Sari (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
ABSTRACT Adolescence is a critical stage of life, so this period is categorized as vulnerable and has health risks. One of the main nutritional problems that are also experienced by many adolescents is anemia. Anemia is a condition in which the number of red blood cells or the level of hemoglobin in red blood cells is below normal. Moglobin (Hb or HGB) is a protein that binds iron (FE2+) as the main component in erythrocytes with the function of transporting O2 and CO2 and giving red color to the blood. Adolescents are at high risk for anemia, especially iron. It is estimated that 25% of Indonesian adolescents are anemic. Although it is not contagious, anemia is very dangerous because it can affect the health status of the future baby. This type of research is a Pre Experiment where the form of design used is One Groups Pretest-Posttest Design. The sampling technique used in this study is purposive sampling where the researcher will take all the female adolescent population. shows the results of the T test obtained a value of 0.000 (P <0.05) meaning Ho is rejected and Ha is accepted, which means that there is an effect on the administration of fruit juice on the increase in Hb in adolescent girls. The results of 20 respondents obtained the mean value of pre-test hemoglobin levels given beetroot juice. of 10.6, standard deviation of 0.388, the results of the minimum hemoglobin level of 10 and the results of the maximum hemoglobin level of 11. And the results of the mean post-test hemoglobin level given beetroot juice of 11.3, the standard deviation of 0.387, the results of hemoglobin levels The minimum is 11 and the maximum hemoglobin level is 12. Key words : Hemoglobin, Anemia, Adolescent